A novel LysR‐type regulator negatively affects biosynthesis of the immunosuppressant brasilicardin. Issue 1 (4th November 2020) - Wolański, Marcin; Krawiec, Michał; Schwarz, Paul N.; Stegmann, Evi; Wohlleben, Wolfgang; Buchmann, Anina; Gross, Harald; Eitel, Michael; Koch, Pierre; Botas, Alma; Méndez, Carmen; Núñez, Luz Elena; et al.
Abstract: Brasilicardin A (BraA) is a promising immunosuppressive compound produced naturally by the pathogenic bacterium Nocardia terpenica IFM 0406. Heterologous host expression of brasilicardin gene cluster showed to be efficient to bypass the safety issues, low production levels and lack of genetic tools related with the use of native producer. Further improvement of production yields requires better understanding of gene expression regulation within the BraA biosynthetic gene cluster (Bra‐BGC); however, the only so far known regulator of this gene cluster is Bra12. In this study, we discovered the protein LysRNt, a novel member of the LysR‐type transcriptional regulator family, as a regulator of the Bra‐BGC. Using in vitro approaches, we identified the gene promoters which are controlled by LysRNt within the Bra‐BGC. Corresponding genes encode enzymes involved in BraA biosynthesis as well as the key Bra‐BGC regulator Bra12. Importantly, we provide in vivo evidence that LysRNt negatively affects production of brasilicardin congeners in the heterologous host Amycolatopsis japonicum . Finally, we demonstrate that some of the pathway related metabolites, and their chemical analogs, can interact with LysRNt which in turn affects its DNA‐binding activity.